2016
DOI: 10.1007/978-3-319-39814-3_16
|View full text |Cite
|
Sign up to set email alerts
|

Anycast and Its Potential for DDoS Mitigation

Abstract: IP anycast is widely being used to distribute essential Internet services, such as DNS, across the globe. One of the main reasons for doing so is to increase the redundancy of the service and reduce the impacts of the growing threat of DDoS attacks. IP anycast can be further used to mitigate DDoS attacks by confining the attack traffic to certain areas. This might cause the targeted service to become unavailable only to a fraction of its users. In this PhD research we aim at investigating how IP anycast can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…It plays a vital role for DNS and CDN and services, but different issues have been noted, including the detection latency of IP anycast prefixes [20], AS-level anycast path inflation [21], and client-server mapping limitations that arise in CDN routing [2]. Several enhancements have been discussed focusing on either performance, see, e.g., [22,23], or security, e.g., to mitigate distributed denial-of-service (DDoS) attacks [5]. It has been shown that anycast routing can achieve near-optimal response times and that it can be tailored to suit the QoS requirements of DiffServ networks [24], but these techniques often require knowledge about the global network state (i.e., router loads) [25,26].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…It plays a vital role for DNS and CDN and services, but different issues have been noted, including the detection latency of IP anycast prefixes [20], AS-level anycast path inflation [21], and client-server mapping limitations that arise in CDN routing [2]. Several enhancements have been discussed focusing on either performance, see, e.g., [22,23], or security, e.g., to mitigate distributed denial-of-service (DDoS) attacks [5]. It has been shown that anycast routing can achieve near-optimal response times and that it can be tailored to suit the QoS requirements of DiffServ networks [24], but these techniques often require knowledge about the global network state (i.e., router loads) [25,26].…”
Section: Related Workmentioning
confidence: 99%
“…A common application involves information retrieval in content-delivery networks (CDN), where user requests can be served from the most appropriated data center hosting a geographically replicated service [1][2][3][4]. This alternative to unicast routing helps to reduce service latency that can originate from normal or intended network congestion, e.g., as produced by a denial-of-service attack [5]. In addition, it helps improve service resiliency to partial network outages [6].…”
Section: Introductionmentioning
confidence: 99%
“…Early studies focused on the first large-scale application of anycast to the DNS [9] [21] [22], and on architectures for creating a global anycast service [3] [4]. More recently, anycast was used as a security tool [23] [6] [24]. Hesselman et al [25] study how to provide a control plane for DNS top-level domain (TLD) operators to increase security and stability of TLDs, while Rizvi et al [8] describe a method for building a "response playbook" for the use of BGP to shift anycast traffic when under DDoS attacks.…”
Section: Related Workmentioning
confidence: 99%
“…In the following years, we expanded our community network around the testbed, deploying anycast sites around the world. Several researches were carried out along the years using the TANGLED network: anycast catchment studies [26] and the tool called VERFPLOETER [27]; and several anti-DDoS studies from [14], [15] were carried out using our testbed. Moreover, the TANGLED testbed is actively being used in the projects SAND [28] and PaaDDoS [29].…”
Section: A Historical Contextmentioning
confidence: 99%

Tangled: A Cooperative Anycast Testbed

Bertholdo,
Ceron,
de Vries
et al. 2020
Preprint
Self Cite